2021
DOI: 10.1155/2021/6653387
|View full text |Cite
|
Sign up to set email alerts
|

circRNA circFAT1(e2) Elevates the Development of Non-Small-Cell Lung Cancer by Regulating miR-30e-5p and USP22

Abstract: Background. As a newly discovered regulatory RNA, circular RNA (circRNA) has become a hot spot in many tumor pieces of research. In recent years, it has been discovered that circRNAs have multiple biological effects in different stages of cancer. However, the expression pattern and mechanism of circFAT1(e2) in non-small-cell lung cancer (NSCLC) are still unclear. Methods. The expressions of circFAT1(e2) in NSCLC tissues and cell lines were studied. Functionally, CCK-8 and transwell experiments were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
2
0
2
Order By: Relevance
“…In contrast to most reports that circFAT1 was present in cytoplasm, it was present in cytoplasm to upregulating tumor suppressor RUNX1 by acting as a sponge for miR-548g, and in nuclei to regulate YBX1 function by physical interaction in gastric cancer [32]. Consistent with our finding, circFAT1 was reported to be upregulated in five NSCLC patients tested, although we found that the reported target miR-30e-5p was reduced by 51% and USP22 mRNA did not change significantly in A549 cells upon shcircFAT1 treatment, instead of an increase of miR-30e-5p by about 4 fold and a reduction of USP22 by half in the report [36]. This discrepancy could be due to different experimental conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to most reports that circFAT1 was present in cytoplasm, it was present in cytoplasm to upregulating tumor suppressor RUNX1 by acting as a sponge for miR-548g, and in nuclei to regulate YBX1 function by physical interaction in gastric cancer [32]. Consistent with our finding, circFAT1 was reported to be upregulated in five NSCLC patients tested, although we found that the reported target miR-30e-5p was reduced by 51% and USP22 mRNA did not change significantly in A549 cells upon shcircFAT1 treatment, instead of an increase of miR-30e-5p by about 4 fold and a reduction of USP22 by half in the report [36]. This discrepancy could be due to different experimental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…While circFAT1 functions as an oncogene in these systems, intriguingly, it is a tumor suppressor in gastric cancer by targeting miR-548g/RUNX1 in cytoplasm and physically interacting with YBX1 protein to block its function in nucleus [32]. Additionally, in vitro studies suggested that circFAT1 could also regulate some cell biological properties by regulating miR-525-5p/ SKA1, miR-181b/HK2, miR-30e-5p/ITGA6 or USP22, miR-873/ZEB1, miR-10a maturation, and miR-21 expression [33][34][35][36][37][38][39], however the in vivo importance and clinic relevance of circFAT1 and its downstream targets in tumorigenesis remain to be determined. These studies indicate that the same circRNA functions to regulate different miRNA targets in different systems, or by other completely different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…6 Compared with normal tissues, circFAT1 was highly expressed in NSCLC tissues. 15 CircFAT1 can promote the progression of HCC through sponge miR-30a-5p and enhancing REEP3. 16 In this study, the expression level of serum circFAT1 was significantly higher in the NSCLC group than in the control group, which coincided with the Ualcan database data and Dong et al 16 conducted basic research, suggesting that high circFAT1 expression accelerated the proliferation, invasion and growth of NSCLC cells, increased oncogenic activity, The presence of excessive lymphocyte infiltration during tumor progression indicates that T cells cannot provide an effective immune response to control tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-30e -к противоположным результатам [43,44]. В качестве механизмов онкосупрессивного действия miRNA-30e предлагают регуляцию осей ITGA6, USP22 ITGA6 / PI3K / AKT и SOX9 [41,[43][44][45].…”
Section: экспериментальная статья | Experimental Reportunclassified
“…miRNA-30e -к противоположным результатам [43,44]. В качестве механизмов онкосупрессивного действия miRNA-30e предлагают регуляцию осей ITGA6, USP22 ITGA6 / PI3K / AKT и SOX9 [41,[43][44][45]. В связи с ключевой ролью miR-30e в патогенезе РЛ было предложено использовать ее для разработки таргетной терапии, тем более что увеличение экспрессии этой микроРНК усиливает чувствительность к терапии гефинитибом [46].…”
Section: экспериментальная статья | Experimental Reportunclassified